Irrigation Scheduling Tips for Tropical Fruit Groves in South Florida: TR001/TR001, rev. 9/2022 - Bayabil, Haimanote K.; Migliaccio, Kati; Crane, Jonathan; Li, Yuncong (EDIS, 2022)
This fact sheet provides irrigation scheduling tips to growers of tropical fruit (e.g., avocado, mango, papaya, etc.) in south Florida. Written by Haimanote K. Bayabil, Kati W. Migliaccio, Jonathan H. Crane, and Yuncong Li, and published by the UF/IFAS Department of Agricultural and Biological Engineering, revised September 2022.